Gathering the Stakeholder’s Perspective: Experiences and Opportunities in Rare Genetic Disease Research - White, Lauren K.; Crowley, T. Blaine; Finucane, Brenda; McClellan, Emily J.; Donoghue, Sarah; Garcia-Minaur, Sixto; Repetto, Gabriela M.; Fischer, Matthias; Jacquemont, Sebastien; Gur, Raquel E.; Maillard, Anne M.; Donald, Kirsten A.; et al. (Genes, 2023)
Background: Research participant feedback is rarely collected; therefore, investigators have limited understanding regarding stakeholders’ (affected individuals/caregivers) motivation to participate. Members of the Genes to Mental Health Network (G2MH) surveyed stakeholders affected by copy number variants (CNVs) regarding perceived incentives for study participation, opinions concerning research priorities, and the necessity for future funding. Respondents were also asked about feelings of preparedness, research burden, and satisfaction with research study participation. Methods: Modified validated surveys were used to assess stakeholders´ views across three domains: (1) Research Study Enrollment, Retainment, Withdrawal, and Future Participation; (2) Overall Research Experience, Burden, and Preparedness; (3) Research Priorities and Obstacles. Top box score analyses were performed. Results: A total of 704 stakeholders´ responded from 29 countries representing 55 CNVs. The top reasons for initial participation in the research included reasons related to education and altruism. The top reasons for leaving a research study included treatment risks and side effects. The importance of sharing research findings and laboratory results with stakeholders was underscored by participants. Most stakeholders reported positive research experiences. Conclusions: This study provides important insight into how individuals and families affected with a rare CNV feel toward research participation and their overall experience in rare disease research. There are clear targets for areas of improvement for study teams, although many stakeholders reported positive research experiences. Key findings from this international survey may help advance collaborative research and improve the experience of participants, investigators, and other stakeholders moving forward.